Pengaruh Pergaulan Teman Sebaya terhadap Tingkat Kenakalan Remaja di Kelurahan Hutabarangan Kota Sibolga - Mei Nita Bela Sari Hutauruk; Rosdiana Rosdiana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The objectives of this study are: 1) to determine the form of peer interaction among adolescents in Hutabarangan Village, Sibolga City 2) to determine the level of juvenile delinquency that occurs in Hutabarangan Village, Sibolga City 3) to see whether there is an influence of peer interaction on the level of juvenile delinquency in Hutabarangan Village, Sibolga City. This study is included in the type of Quantitative Descriptive research. The sample used was 35 adolescents with an age range of 13-17 years in Hutabarangan Village. The sampling technique chosen was Purposive Sampling based on certain considerations and criteria. Data were collected through questionnaires, then analyzed using simple linear regression. From the results of the analysis, it is known that there is an influence of peer interaction on the level of juvenile delinquency in Hutabarangan Village. The form of peer interaction in Hutabarangan Village is classified as very high with a percentage of 54.3%, while the level of juvenile delinquency in Hutabarangan Village is classified as high with a percentage of 57.1%. The calculation results show that the t_count value = 6.440 and t_table = 1.692 at a significance level of 0.005 (5%). Because t_count > t_table, it can be concluded that H0 is rejected and Ha is accepted. This indicates that there is an influence of peer interaction on the level of juvenile delinquency. The coefficient of determination obtained is 55.7%. This means that the magnitude of the influence of peer interaction on the level of juvenile delinquency is 55.7% while the remaining 44.3% is influenced by other variables not examined in this study.